PENGARUH ETIKA BISNIS ISLAM DAN RELATIONSHIP MARKETING TERHADAP CUSTOMER RETENTION PADA BANK SUMSEL BABEL CABANG SYARIAH PALEMBANG - Adelia Novriani; Hilda; Lemiyana (ITB AAS Indonesia Surakarta, 2026)
This research was conducted with the aim of testing and analyzing the influence of Islamic business ethics and Relationship Marketing on Customer Retention at Bank Sumsel Babel, Sharia Branch, Palembang. This research uses quantitative methods using primary data. Data were collected through distributing questionnaires to customers. The population in this study were customers of Bank Sumsel Babel, Sharia Branch, Palembang with a total of 43,530, the sample used in this study was 100 respondents with a purposive sampling technique. Data analysis techniques used validity tests, normality tests, reliability tests, classical assumption tests, multiple linear regression tests and hypothesis tests using the help of the IBM SPSS version 26 application. The results of the study indicate that Islamic business ethics affect Customer Retention, Relationship Marketing affects Customer Retention. Simultaneously, Islamic business ethics and Relationship Marketing affect Customer Retention.